Upsilon invariants from cyclic branched covers - Alfieri, A; Celoria, D; Stipsicz, A (Akadémiai Kiadó, 2021)
We extend the construction of Y-type invariants to null-homologous knots in rational homology three-spheres. By considering m-fold cyclic branched covers with m a prime power, this extension provides new knot concordance invariants YCm(K) of knots in S3. We give computations of some of these invariants for alternating knots and reprove independence results in the smooth concordance group.